Therapeutic Effect of Phaleria macrocarpa Flavonoid Extract on TGF-β Modulation in Endometriosis Mice Model - Novrida Ratna Dewi; Cyntia Hemas Febrina Putri; Sutrisno Sutrisno; Safrina Dewi Ratnaningrum (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Endometriosis is a chronic estrogen-dependent inflammatory disorder characterized by ectopic endometrial-like tissue growth and dysregulated immune responses. Transforming Growth Factor Beta (TGF-β), although classically known as a profibrotic cytokine, also exhibits context-dependent anti-inflammatory activity, creating uncertainty regarding its net impact on endometriotic progression. This gap in the literature highlights the need to investigate agents that may modulate TGF-β in a controlled experimental setting. Phaleria macrocarpa, a flavonoid-rich medicinal plant, has demonstrated immunomodulatory potential, yet its relationship with TGF-β regulation in endometriosis remains poorly understood. This study aimed to evaluate the effect of Phaleria macrocarpa flavonoid extract on TGF-β levels in a Balb/C mouse model of endometriosis. A true experimental post-test only controlled design was conducted using 30 mice divided into six groups: negative control, positive control, and four treatment groups receiving 3.75, 7.5, 15, or 30 mg/mouse/day for 14 days. TGF-β levels were quantified using ELISA and analyzed with ANOVA followed by Tukey’s post-hoc test. The results demonstrated a non-linear dose–response pattern, with the 7.5 mg/mouse/day dose producing the highest increase in TGF-β, while higher doses showed attenuated or reduced responses. These findings indicate a biphasic modulatory effect of Phaleria macrocarpa flavonoids on TGF-β, suggesting a dose-dependent immunoregulatory influence that warrants further investigation. Keywords: Phaleria macrocarpa, TGF-β, Endometriosis, Mice.